Can bony labyrinth dimensions predict biological sex in archaeological samples?. (June 2020) - Ward, Devin L.; Pomeroy, Emma; Schroeder, Lauren; Viola, T. Bence; Silcox, Mary T.; Stock, Jay T.
Highlights: Labyrinthine shape did not correspond with assessed sex in archaeological groups. Cultural and dietary differences in archaeological groups had no effect. Use of a previously-published equation or of raw measurements had no effect. Bony labyrinth shape variation within humans is present, but not fully explored. Abstract: Osipov and colleagues [ American Journal of Physical Anthropology, 2 (151) 2013] previously posited that the dimensions of the bony labyrinth exhibit sexual dimorphism. Using a recent sample of known sex, they produced an age-independent, multivariate equation to predict biological sex using several of these dimensions. We aim to test the applicability of this equation to archaeological samples, where the method could prove useful with poorly preserved remains. Using µCT data, we collected a standard set of linear dimensions from the bony labyrinth in two groups from the ancient Nile Valley that show body size differences associated with diet and disease. We determined the biological sex of these individuals using established skeletal features and with Osipov and colleagues' (2013) equation. Results of each were compared with McNemar tests, and raw measurements were examined within each group for dimorphism with a Discriminant Function Analysis. Biological sex predicted by labyrinthine dimensions overidentified individuals from both groups as female. Adjustments to the equation constant balanced predicted sex numbers and increased consistency both on an individual level (31.3% to 67.4%) and model level (χ 2  < critical value). Discriminant function analysis consistently classified 60% of el-Badari and 50% of Kerma individuals. Absolute bony labyrinth dimensions and the results of Osipov and colleagues' (2013) equation did not produce sex estimations consistent with those made from assessment of pelvic and cranial features. As these assessments also have error, further exploration of sexual dimorphism in the labyrinth should be undertaken in collections with known sex.